Awareness of tumor suppressor genes among dental students - Patturaja, Kiruthika; Ganapathy, Dhanraj; Duraisamy, Revathi (International Journal of Psychosocial Rehabilitation, 2020)
Tumor formation arises as a consequence of alterations in the control of cell proliferation and disorders in the interactions between cells and their surroundings that result in invasion and metastasis. Tumor suppressor genes activate a multitude of genes encoding proteins with functions in cell-cycle control, DNA repair, senescence, and apoptosis. The present study aims to find the awareness of tumor suppressor genes among dental students. An online questionnaire was formulated and distributed among 215 dental students in Saveetha Dental College, Chennai, pursuing undergraduate and postgraduate courses. Of 215 students, 200 students responded. A total of 10 multiple-choice questions were formulated and distributed. Data were collected from the filled questionnaire and analysed. Descriptive statistics were done using SPSS statistical analysis. The results of the present study findings show that there was no significant association between undergraduate and postgraduate dental students on awareness of tumour suppressor genes (p = 0.174). The overall awareness level of tumour suppressor genes among dental students was moderate. This study showed that the awareness of tumor suppressor genes was moderate among the dental students. Increased importance should be given to education in this aspect of tumor suppressor genes.